Drug abuse, HIV/AIDS and stigmatisation in a Dai community in Yunnan, China - Deng, R.; Li, Jianghong; Sringernyuang, L.; Zhang, K. (Elsevier Science, 2007)
The latest data indicate that between 540,000 and 760,000 people are infected with HIV in China. Although minority nationalities represent 8.1% of China's total population, they account for more than 30% of the reported HIV/AIDS cases. This study examined stigma and discrimination against drug abusers and people living with HIV/AIDS (PLHA) in a Dai minority nationality community in Yunnan, China. The study used qualitative research methods, which included participatory observations, in-depth interviews, focus-group discussions, transect walking and community mapping. A combination of different sampling strategies was used to maximise diversity of the initially selected sample. The data revealed deeply entrenched stigma and overt discrimination against drug abusers and PLHA that manifested in familial, work, civil and institutional contexts. The stigma reflected pre-existing cultural, religious sanctions against “deviant behaviours”. Intervention programmes that were insensitive to the local culture and religion may have also contributed in part to the stigmatisation of drug abusers and PLHA. The major impact of stigma was that it created a vicious cycle of social isolation, marginalisation and thus addiction relapse. This in turn reinforced the stigmatisation and discrimination against drug abusers and thus hindered efforts towards prevention and control of HIV/AIDS.